The influence of processing sequence and frozen storage on the seasoned alaska pollack (Theragra chalcogramma) roe product quality. (30th March 2022) - Chen, Chaoping; Geng, Jie-Ting; Thanathornvarakul, Nonthacha; Keratimanoch, Sumate; Üçyol, Nail; Okazaki, Emiko; Osako, Kazufumi
Highlights: The effect of processing sequence on the quality of roe product was investigated. Protein degradation of the eggshell was the cause of textural damage. Cryoprotectants in seasoning solution prevented product quality deterioration. The Seasoning-Frozen storage processed roe product superior quality. Abstract: The quality of seasoned products of Alaska pollack ( Theragra chalcogramma ) roe declined dramatically during frozen storage. This research investigated the effects of processing sequence and frozen storage period on seasoned Alaska pollack roe product quality. In addition, the relationship between mechanical properties and protein composition of ovary membrane and eggshell was discussed. The seasoned roe product made by the Seasoning-Frozen storage process showed higher mechanical property values, better surface color and more stable protein composition. The results clarified that this process allowed endogenous transglutaminase to act before it had been denatured and effectively prevented protein degradation during frozen storage. The retardation of protein degradation was probably attributed to cryoprotective effects from components in seasoning solution.